ОБРАЗ НАНА В ЗБІРЦІ ВІРИ ВОВК «ЖІНОЧІ МАСКИ» ЯК ПСИХОЛОГІЧНА МОДЕЛЬ У ЗІСТАВЛЕННІ ЗІ СВІТОВИМ КОНТЕКСТОМ: ПОЄДНАННЯ НАТУРАЛІЗМУ І НЕОМІФОЛОГІЗМУ - Смольницька, Ольга (Збірник наукових праць Уманського державного педагогічного університету, 2020)
У статті здійснено компаративний аналіз вірша Віри Вовк «Нана» у зіставленні з романом Еміля Золя, на основі якого створено даний верлібр збірки «Жіночі маски». Мета дослідження полягає в аналізі використання прийомів натуралізму (школа Золя) і неоміфологізму як ознаки стилю В. Вовк. Використані методи: поетологічний, компаративний, культурологічний, фройдистський, біографічний. Досліджено мотивацію вибору письменниці – інтерпретацію образу неромантичної героїні Золя. Наведено історичний контекст образу героїні в контекстуальному розрізі. В статье осуществлен компаративный анализ стихотворения Веры Вовк «Нана» в сопоставлении с романом Эмиля Золя, на основе которого создан данный верлибр сборника «Женские маски». Цель исследования заключается в анализе использования приемов натурализма (школа Золя) и неомифологизма как признаки стиля В. Вовк. Используются методы: поэтологический, компаративный, культурологический, фрейдистский, биографический. Исследуется мотивация выбора писательницы – интерпретация образа неромантической героини Золя. Приведен исторический контекст образа героини в контекстуальном разрезе. The article investigates a comparative analysis of the poem by Vira Vovk «Nana» in comparison with the having the same name novel by Emile Zola, because of it is base of this vers libre of the collection «Feminine Masks» is created. The purpose of the research is the analysis of the use of the techniques of naturalism (Zola school) and neomythologism as marks of style by V. Vovk. There are such methods used: poetological, comparative, cultural, Freudian, biographical. Especially, the comparative analysis of the novels by Honoré de Balzac, the novel by Anatole France «The Gods Are Athirst», the story by Alexander Kuprin «The Pit» («Yama») and the famous courtesans as prototypes of Nana is made. The motivation of the choice of the Ukrainian writer in Brazil is provided which is based on her own interpretation of the non-romantic image of Zola’s heroine. The historical context of the image of Nana in the contextual aspect is given.